Developments in surface contamination and cleaning. Volume five, Contaminant removal and monitoring - Kohli, Rajiv, 1947-; Mittal, K. L., 1945- (Amsterdam ; Boston : William Andrew, 2013)
In this series, Rajiv Kohli and Kash Mittal have brought together the work of experts from different industry sectors and backgrounds to provide a state-of-the-art survey and best-practice guidance for scientists and engineers engaged in surface cleaning or dealing with the consequences of surface contamination. This volume complements Volumes 3 and 4 of this series, which focused largely on particulate contaminants. The expert contributions in this volume cover methods for removal of non-particulate contaminants, such as metallic and non-metallic thin films, hydrocarbons, toxic and hazardous chemicals, and microbiological substances, as well as contamination monitoring in pharmaceutical manufacturing, and an innovative method for characterization at the nanoscale. Feature: Comprehensive coverage of innovations in surface contamination and cleaning Benefit: One-stop series where a wide range of readers will be sure to find a solution to their cleaning problem, saving the time involved in consulting a range of disparate sources. Feature: Written by established experts in the contamination and cleaning field Benefit: Provides an authoritative resource Feature: Each chapter is a comprehensive review of the state of the art. Benefit: Can be relied on to provide insight, clarity and real expertise on up-to-the-minute innovations. Feature: Case studies included Benefit: Case studies help the reader see theory applied to the solution of real-world practical cleaning and contamination problems.
Title from PDF title page (viewed on Oct. 24, 2012).
Includes bibliographical references and index.
Keywords: Surfaces (Technology) -- Inspection; Surface contamination -- Prevention; Cleaning; Coatings; TECHNOLOGY & ENGINEERING -- Nanotechnology & MEMS; Cleaning; Coatings; Surfaces (Technology) -- Inspection